2006
DOI: 10.1111/j.1540-627x.2006.00155.x
|View full text |Cite
|
Sign up to set email alerts
|

Government Public Policy, Regulatory Intervention, and Their Impact on IPO Underpricing: The Case of Malaysian IPOs

Abstract: This study examines the impact of government initial public offering (IPO) regulation intending on promoting public policy. The study examines the results of the implementation of a Malaysian government policy in 1976, which mandated that at least 30 percent of any new shares on an IPO offer be sold to the indigenous Bumiputera population or to mutual funds owned by them. The study examined the short-run and long-run underpricing of Malaysian IPOs and found that Malaysian IPOs are highly underpriced compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 46 publications
5
20
0
Order By: Relevance
“…For instance, Prasad et al (2006) found that a government's regulatory intervention in spite of noble public policy intentions, appeared to be the significant factor for the emergence of an average first day underpricing increase of private Malaysian IPOs of 61% during the period after a specific regulatory economic policy which mandated that at least 30% of any new shares on any private IPO offer were to be sold to the indigenous Bumiputera population or to mutual funds owned by them. Furthermore, their study found that this high underpricing persisted even for the long-run, in contrast to the long-run performance of IPOs in the USA.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…For instance, Prasad et al (2006) found that a government's regulatory intervention in spite of noble public policy intentions, appeared to be the significant factor for the emergence of an average first day underpricing increase of private Malaysian IPOs of 61% during the period after a specific regulatory economic policy which mandated that at least 30% of any new shares on any private IPO offer were to be sold to the indigenous Bumiputera population or to mutual funds owned by them. Furthermore, their study found that this high underpricing persisted even for the long-run, in contrast to the long-run performance of IPOs in the USA.…”
Section: Resultsmentioning
confidence: 98%
“…Three of these considerations are likely to affect the investment banker's decision on the offer price. Governments would like to intentionally underprice an offer to improve the chance of success of the offer (since failure would have serious political costs for the ruling government party), to promote greater share ownership for egalitarian, welfare promotion, and social public policy reasons (Prasad, Vozikis, & Ariff, 2006), and finally as an incentive or a down payment to increase the probability of participation in successive issues of privatization programs. The third reason is to protect the issuer's reputation more than the investment banker's reputation as discussed by Beatty and Ritter (1986).…”
Section: Theories Of Underpricing and Privatized Firmsmentioning
confidence: 99%
“…In addition to the review work by of the initial returns on IPOs in thirty-eight countries between 1959 and 2003, other recent (since 2004) studies on IPOs using non-U.S. data include studies on Malaysian IPOs by Prasad, Vozikis, and Ariff (2006) and Ahmad-Zaluki, Campbell, and Goodacre (2007); on Canadian Unit Trust IPOs by Boabang (2005); on Egyptian IPOs by Omran (2003); and on Chinese IPOs by Chan, Wan, and Wei (2004) and Padgett (2005, 2006). Several explanations have been offered in literature to explain the phenomenon of underpricing.…”
Section: Review Of Relevant Literaturementioning
confidence: 98%
“…According to García-Ayuso (2003), companies that disclose less IC information than analysts expect may broaden the information gap, leading to information and valuation crises such as those faced by capital markets in 1997-2003 (Holland &Johanson, 2003). This fact is especially important in the Malaysian IPO setting, where empirical studies on IPO underpricing are significantly higher in the past (Prasad et al, 2006;Uddin, 2008). Furthermore, the underpricing phenomenon is recognised as the major cost of capital for an IPO (Singh & Van der Zahn, 2007).…”
Section: Ic Disclosure In Ipo Prospectusesmentioning
confidence: 99%
“…Unlike previous studies that tended to focus on the determinants of IC disclosure, this study adopts the perspective of non-disclosure of IC information. Even though this line of inquiry has received very little attention from IC researchers, it is equally important given that IPOs in Malaysia are highly underpriced compare to IPOs in other developing countries and generally have low levels of IC disclosure (Prasad et al, 2006;Warn &Somasundaram, 2010). There is limited and inconclusive evidence on the reasons for non-disclosure of IC information, particularly in the Malaysian IPO setting.…”
Section: Ic Disclosure In Ipo Prospectusesmentioning
confidence: 99%